Nkx2.1 downregulation is involved in brain abnormality induced by excess retinoic acid. (23rd May 2020) - Jia, Sansan; Zhang, Li; Zhang, Kaili; Wang, Lei; Khan, Ajab; Zhang, Juan; Sun, Yuqing; Wang, Yufei; Song, Meiyan; Lyu, Yi; Li, Meining; Lu, Xin; et al.
Abstract: Abnormal development of central nervous system (CNS) caused by neural tube defects is not only a major contributor in the prevalence of stillbirths and neonatal deaths but also causes lifelong physical disability in surviving infants. Due to insufficient known investigated causes, CNS developmental abnormality has brought sever burden on health around the world. From previous results of high throughput transcriptome sequencing, we selected transcription factor Nkx2.1 as a candidate to investigate its role on brain abnormalities induced by excessive retinoic acid. The result of in situ hybridization showed that Nkx2.1 was mainly expressed in mouse brain. After the Nkx2.1 gene was silenced, retarded proliferation and accelerated apoptosis were found in mouse Neuro-2a (N2a) cells. Furthermore, our results indicated that the main components of sonic hedgehog (Shh) signaling pathway were affected in Nkx2.1 -silenced cells, implying that Nkx2.1 plays an important role in the development of mouse brain by regulating Shh signaling pathway.